(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Anti-inflammatory drugs are among the most widely prescribed pharmacological agents in modern medicine, used for the management of pain, fever, and inflammatory conditions ranging from arthritis to post-operative tissue injury. Despite their therapeutic efficacy, these drugs — both steroidal and nonsteroidal — are associated with a broad spectrum of adverse effects that can compromise patient safety, particularly with chronic use. The mechanisms underlying these side effects are complex, involving inhibition of prostaglandin synthesis, alterations in immune response, endocrine disruption, and gastrointestinal or renal toxicity. This article provides a comprehensive overview of the side effects of anti-inflammatory drugs, emphasizing their pathophysiological basis, clinical manifestations, and strategies for minimizing harm through rational pharmacotherapy and monitoring.